Development of Physics Teaching Materials Based on I-SETS (Islamic, Science, Environment, Technology, Society) to Improve Students' Critical Thinking Skills - Sri Wahyuni; Muhammad Arsyad; Khaeruddin Khaeruddin (Postgraduate, University of Mataram, 2024)
Research has been carried out on the development of I-SETS (Islamic, Science, Environment, Technology, Society) based teaching materials to improve students' critical thinking skills which aims to describe the suitability of I-SETS based teaching materials, practitioners' assessments of I-SETS based teaching materials, increasing students' critical thinking skills, and producing I-SETS based teaching materials. This research uses 4D model development. The instruments used in this research were teaching material validation sheets, practitioner assessment questionnaires, and students' critical thinking skills test instruments. The practicality criteria are seen from practitioners' assessments of teaching materials, and the effectiveness criteria are seen from the increase in critical thinking skills which are analyzed using the N-gain equation. Based on the results of the analysis, conclusions were drawn: I-SETS based teaching materials developed based on expert assessment using Aiken's V index analysis were declared valid and suitable for use with minor revisions; I-SETS based teaching materials in terms of practitioner/teacher responses are in the very good category; The effectiveness of I-SETS based teaching materials is obtained from the results of students' critical thinking skills tests analyzed using N-gain with an average score of 0.56 in the medium category, which means that there is an increase in students' critical thinking skills so it can be said that the teaching materials The developed I-SETS is effective and can improve students' critical thinking skills.